Knowledge, attitude and practice towards COVID-19 pandemic among patients attending dental outpatient department of M.G.M. Medical College and Hospital, Jamshedpur, Jharkhand, India - Anvita Sinha; Nitesh Kumar Sharma; Sudhanshu Saxena; Sonia Tiwari; Anushree Prasad; Pooja Kumari; Mousami Kundu (Wolters Kluwer Medknow Publications, 2023)
Background: The 2019 coronavirus disease (COVID-19) is an extremely contagious illness that spreads mostly via the dentistry practice. Patients in need of dental care are at a higher risk of becoming infected with and becoming carriers of the illness. Aim: To assess the COVID-19-related knowledge, attitude, and practice (KAP) of patients visiting dental outpatient department of M.G.M. Medical College and Hospital, Jamshedpur, Jharkhand, India. Materials and Methods: In this cross-sectional study, patients visiting dental outpatient department of M.G.M. Medical College and Hospital, Jamshedpur, Jharkhand, India were included. The questionnaire had four sections including demographic information, knowledge, attitudes, and practice in relation to COVID-19. Along with computation of descriptive statistics, data analysis was performed using unpaired t-test. Results: A total of 332 people took part in the research. The female respondents were higher in number (53.01%) and the highest percentage of the respondents belongs to the age group 18-40 years (55.72%). Nearly, 98% of respondents were vaccinated. The highest percentage of KAP level was recorded for knowledge (74.95%) followed by that of attitude (50.84%) and practices (37.05%). Conclusion: While respondents' overall knowledge was high but their enthusiasm for taking preventative measures was low, and their efforts to stem the pandemic were lagging at best. Future campaigns should focus more on reaching out to marginalized populations, such as those with less education or higher poverty rates.